PERTUMBUHAN TAMANAN TOMAT PADA PENGARUH CEKAMAN NATRIUM CLORIDA (NaCl) - Abdullah Sarijan; Nurhening Ekowati (AGRICOLA, 2012)
Research on Tomato Plant Growth Effect of stress on Sodium Clorida (NaCl) was undertaken for 3 months at the Agriculture Faculty, Musamus Merauke University. The study aims to see the effect of Sodium Clorida (NaCl) on tomatoes plant growth. The treatment is applied in four levels of NaCl concentrations of 0 g/litre of water (0 PPM), 2 g /litre of water (2000 PPM), 4 g/litre of water (4000 PPM) and 6 g/litre of water (6000 PPM). The results showed that the observation of vegetative growth (plant height and number of branches of leaves), NaCl treatment give effect to the age of 4 and 5 weeks after planting, whereas for the observation of generative growth (flower number and fruit number), NaCl to influence the amount of interest on ages 5, 6 and 7 weeks after planting, and the amount of fruit at the age of 8 and 9 weeks after planting. In the ninth week of observation found that the plants are dried up 75% (27 plants) to treatment with NaCl content of 6000 PPM; 52.8% (19 plants) for the treatment of NaCl content of 4000 PPM, and 13.9% (5 plants) for the treatment NaCl content of 2000 PPM, while the 0 PPM NaCl treatment did not found the plants to dry out. Plants that are dry or death caused by high NaCl concentration in the soil so that plants are unable to take nutrients from the soil solution and vice versa due to high salinity in the soil resulting in the body fluids of plants absorbed out. The interesting thing about this study is that treatment with higher levels of NaCl apparently produce more amount of interest that need further examination of the NaCl treatment to induce flowering. Besides, studies such as this is deemed necessary to be done with the NaCl concentration is lower. The conclusion from this study that the treatment levels of NaCl is applied to give effect to the growth of tomato plants.